Cass Gilbert papers - Gilbert, Cass, 1859-1934.; Gilbert, Cass, 1894-
Correspondence, diaries, speeches, poems, articles, biographical material, financial records, and other papers relating primarily to Gilbert's career as an architect and to the Gilbert family. Correspondence pertains chiefly to his architectural plans for the Federal Courts Building (New York, N.Y.), New York Life Insurance Building (New York, N.Y.), Woolworth Building (New York, N.Y.), United States Chamber of Commerce Building (Washington, D.C.), United States Supreme Court Building (Washington, D.C.), United States Treasury Annex (Washington, D.C.), Arkansas State Capitol (Little Rock, Ark.), Minnesota State Capitol (Saint Paul, Minn. : 1905- ), and the West Virginia Capitol Complex (Charleston, W. Va.). The correspondence also reflects Gilbert's interest in national and international political affairs. Includes correspondence of Gilbert's wife, Julia Finch Gilbert; his brother, Samuel Gilbert; and other family members as well as letterbooks of Cass Gilbert, Jr. Also includes letters (1801-1804) addressed to Thomas Jefferson by James R. Dermott and William Thornton. Gilbert's correspondents include Edwin Howland Blashfield, Nicholas Murray Butler, Arthur Cope, Kenyon Cox, Daniel Chester French, Edward Mandell House, J.J. Jusserand, Charles Moore, Elihu Root, and Sir Aston Webb.
Library of Congress Prints and Photographs Division.
Architect.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blashfield, Edwin Howland, -- 1848-1936 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Cope, Arthur -- Correspondence; Cox, Kenyon, -- 1856-1919 -- Correspondence; Dermott, James R. -- Correspondence; French, Daniel Chester, -- 1850-1931 -- Correspondence; Gilbert, Julia Finch, -- 1862-1952 -- Correspondence; Gilbert, Samuel, -- approximately 1865- -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Thornton, William, -- 1759-1828 -- Correspondence; Webb, Aston, -- Sir, -- 1849-1930 -- Correspondence; Gilbert family; Gilbert family -- Correspondence; United States. -- Department of the Treasury -- Buildings; United States. -- Supreme Court -- Buildings; Arkansas State Capitol (Little Rock, Ark.); Chamber of Commerce of the United States of America -- Buildings; Federal Courts Building (New York, N.Y.); Minnesota State Capitol (Saint Paul, Minn. : 1905- ); New York Life Insurance Company -- Buildings; West Virginia Capitol Complex (Charleston, W. Va.); Woolworth Building (New York, N.Y.); Architecture; Architecture -- Arkansas -- Little Rock; Architecture -- Minnesota -- Saint Paul; Architecture -- New York (State) -- New York; Architecture -- United States; Architecture -- Washington (D.C.); Architecture -- West Virginia -- Charleston; Buildings -- New York (State) -- New York; Public buildings -- Arkansas -- Little Rock; Public buildings -- Minnesota -- Saint Paul; Public buildings -- New York (State) -- New York; Public buildings -- Washington (D.C.); Public buildings -- West Virginia -- Charleston; World politics; United States -- Foreign relations; United States -- Politics and government; Architects